2020
DOI: 10.1002/chem.202000309
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of an Innovative Insulin Analogue Excludes Protracted Action yet Highlights the Distinction between External and Internal Diselenide Bridges

Abstract: Long‐acting insulin analogues represent the most prescribed class of therapeutic proteins. An innovative design strategy was recently proposed: diselenide substitution of an external disulfide bridge. This approach exploited the distinctive physicochemical properties of selenocysteine (U). Relative to wild type (WT), Se‐insulin[C7UA, C7UB] was reported to be protected from proteolysis by insulin‐degrading enzyme (IDE), predicting prolonged activity. Because of this strategy's novelty and potential clinical imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…We found that the substitution of native/non-native disulfide with diselenide bonds typically enhances protein folding and yield, preserves protein structure and often confers no significant effect on function. Based on these results, the current study of the selenohirudin analogues extends the previous studies on selenocysteinecontaining analogues of BPTI 34,35 , conotoxins [28][29][30][31] and insulin [53][54][55] , which together demonstrate the high potential of disulfide-todiselenide substitutions in basic and applied research. In addition to its obvious advantage in the study and preparation of disulfiderich proteins, such an approach may also prove useful for a wide range of applications, including the rational improvement of the stability, activity and specificity of this unique and medically important family of proteins.…”
Section: Discussionsupporting
confidence: 75%
“…We found that the substitution of native/non-native disulfide with diselenide bonds typically enhances protein folding and yield, preserves protein structure and often confers no significant effect on function. Based on these results, the current study of the selenohirudin analogues extends the previous studies on selenocysteinecontaining analogues of BPTI 34,35 , conotoxins [28][29][30][31] and insulin [53][54][55] , which together demonstrate the high potential of disulfide-todiselenide substitutions in basic and applied research. In addition to its obvious advantage in the study and preparation of disulfiderich proteins, such an approach may also prove useful for a wide range of applications, including the rational improvement of the stability, activity and specificity of this unique and medically important family of proteins.…”
Section: Discussionsupporting
confidence: 75%
“…4 We found that the substitution of native/non-native disulfide with diselenide bonds typically enhances protein folding and yield, preserves protein structure, and often confers no significant effect on function. Based on these results, the current study of the seleno-hirudin analogs extends the previous studies on selenocysteine-containing analogs of BPTI, 33,34 conotoxins, [27][28][29][30] and insulin, [52][53][54] which together demonstrate the high potential of disulfide-to-diselenide substitutions in basic and applied research. In addition to its obvious advantage in the study and preparation of disulfide-rich proteins, such an approach may also prove useful for a wide range of applications, including the rational improvement of the stability, activity and specificity of this unique family of proteins.…”
Section: Discussionsupporting
confidence: 74%
“…The degradation of A7–B7 diselenide insulin with insulin-degrading enzyme was reported to be significantly increased and thus the lifetime enhanced. However, a more recent evaluation indicated that the diselenide insulin analogue, in fact, did not have increased stability . This requires further examination and clarification.…”
Section: Chemically Diverse Analoguesmentioning
confidence: 97%
“…However, a more recent evaluation indicated that the diselenide insulin analogue, in fact, did not have increased stability. 175 This requires further examination and clarification. An intra-A-chain diselenide variant of human insulin, A6− A11 diselenide insulin, was also prepared by Metanis and colleagues (Scheme 26).…”
Section: Diselenide Insulinsmentioning
confidence: 99%